Persepsi Siswa Terhadap Kolaborasi Guru Dalam Proses Pembelajaran Pendidikan Agama Islam - Lukman Asha (Tarbawiyah Jurnal Ilmiah Pendidikan, 2022)
One of the breakthroughs in the realm of education management is the massive discourse on teacher collaboration as an effort to improve students' betterment in learning. Thus, this qualitative research aimed to investigate the perceptions of students, from a high school in Rejang Lebong Regency, about the practice of teacher collaboration which had previously been carried out for 10 meetings on the subject of Islamic education. 15 students were selected purposively and involved as the participants. They were interviewed on an ongoing basis. The interview data were then analyzed using an interactive model. The study’s findings mapped students' perceptions of teacher collaboration into several themes and sub-themes. First, the students perceived that teacher collaboration supported collaborative learning, in which collaborative learning contributed to students' critical thinking skills, intercultural competence, and problem-solving skills. Second, teacher collaboration increased students’ learning awareness. Third, teacher collaboration contributed to the improvement of students' metacognition. This study has raised the essence of teacher collaboration variables, such as collaborative learning, critical thinking skills, intercultural competence, problem-solving skills, learning awareness, and metacognition. Further research can conduct psychometric analyses of these variables for the sake of developing a new theoretical model for the construct of teacher collaboration.